2021
DOI: 10.1080/09712119.2021.1946402
|View full text |Cite
|
Sign up to set email alerts
|

PrebioticsBLS from encapsulated of extract of shrimp waste bioconversion on feed supplement quality and its implication of metabolizable energy and digestibility at Indonesian local chicken

Abstract: BLS from encapsulated of extract of shrimp waste bioconversion on feed supplement quality and its implication of metabolizable energy and digestibility at Indonesian local chicken,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The efficiency of the use of feed by fish shows the value (percentage) of food that can be utilized by the animal's body [9]. The efficiency of feeding is directly proportional to the addition of body weight, so the higher the value of feeding efficiency means the more efficient the fish use the feed consumed for growth [10].…”
Section: Results and Discussion A Feed Efficiencymentioning
confidence: 99%
“…The efficiency of the use of feed by fish shows the value (percentage) of food that can be utilized by the animal's body [9]. The efficiency of feeding is directly proportional to the addition of body weight, so the higher the value of feeding efficiency means the more efficient the fish use the feed consumed for growth [10].…”
Section: Results and Discussion A Feed Efficiencymentioning
confidence: 99%
“…The digestibility of a feed ingredient is a reflection of the high low value of the benefits of the feed ingredient. If the digestibility is low, the benefit value is low, on the other hand, if the digestibility is high, the benefit value is also high [4,8,18] . Digestibility that has a high value reflects the large contribution of certain nutrients in livestock, while feed that has a low digestibility value indicates that the feed is less able to supply nutrients for basic living and production [19,20] .…”
Section: Resultsmentioning
confidence: 99%
“…Good quality feeding will result in a good growth response. Good feed is feed that is formulated to meet all the nutritional needs of livestock, has good digestibility, and does not hurt livestock [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is reported that some types of lactic acid bacteria have both properties, as with Bacillus [15]. Bacillus can also inhibit bacteria and has been widely applied in aquaculture [40][41][42].…”
Section: Antimicrobial Activitymentioning
confidence: 99%